Topographical Distribution of Carcinoma Larynx (Bangladesh Journal of Otorhinolaryngology, 2020)
The larynx is the most common site for primary tumour of the head and neck region. It represents world wide approximately 1-2% of all cancers. A cross sectional study of 154 cases of laryngeal carcinoma was carried out in the in-patient department of Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College during the period of two years with an aim to find out the frequency of site and subsite involvement of carcinoma of the larynx. The age range is 33-80 years and the over all male to female ratio is 29.8:1. Smoking and chewing habit are the most important associated factors. Majority of growths are found to be exophytic and most of the patients present at advanced stage. The commonest site of laryngeal carcinoma is supraglottic region and occurrence of supraglottic carcinoma than glottic carcinoma is statistically highly significant.Bangladesh J Otorhinolaryngol; April 2018; 24(1): 56-61